Whole Genome Sequencing and Spatial Analysis Identifies Recent Tuberculosis Transmission Hotspots in Ghana - Asare, Prince; Otchere, Isaac Darko; Bedeley, Edmund; Brites, Daniela; Loiseau, Chloé; Baddoo, Nyonuku Akosua; Asante-Poku, Adwoa; Osei-Wusu, Stephen; Prah, Diana Ahu; Borrell, Sonia; Reinhard, Miriam; Forson, Audrey; et al. (Frontiers in Medicine, 2020)
Whole genome sequencing (WGS) is progressively being used to investigate the transmission dynamics of Mycobacterium tuberculosis complex (MTBC). We used WGS analysis to resolve traditional genotype clusters and explored the spatial distribution of confirmed recent transmission clusters. Bacterial genomes from a total of 452 MTBC isolates belonging to large traditional clusters from a population-based study spanning July 2012 and December 2015 were obtained through short read next generation sequencing using the illumina HiSeq2500 platform. We performed clustering and spatial analysis using specified R packages and ArcGIS. Of the 452 traditional genotype clustered genomes, 314 (69.5%) were confirmed clusters with a median cluster size of 7.5 genomes and interquartile range of 4-12. Recent tuberculosis (TB) transmission was estimated as 24.7%. We confirmed wide spread of a Cameroon sub-lineage clone with cluster size of 78 genomes predominantly from the Ablekuma sub-district of Accra metropolis. More importantly, we identified a recent transmission cluster associated with isoniazid resistance belonging to the Ghana sub-lineage of lineage 4. WGS was useful in detecting unsuspected outbreaks hence we recommend its use not only as a research tool but as a surveillance tool to aid in providing the necessary guided steps to track, monitor and control TB.